Ketika Retorika Mengalahkan Realita: Kebijakan Kriminal di Era Manipulasi Data Publik - Zul Khaidir Kadir (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2025)
Manipulation of public data in criminal policy is a strategic practice that selects and frames information to cover up institutional violations, and legitimizes repressive policies that ignore the principle of justice. Unfortunately, the development of communication technology has accelerated the circulation of information, leading to the birth of repressive policies based on popularity and distorted narratives. This study uses a qualitative research method with a conceptual approach. The data collection method was collected using library research, then analyzed using qualitative methods and presented descriptively. The results of the study indicate that manipulation of public data in criminal policy shifts the orientation of policy from fact-based rationality to biased emotional responses, so that it not only widens inequality and creates selective law enforcement, but also damages institutional legitimacy and erodes public trust in the criminal justice system. A transformative mitigation strategy is needed institutionally and culturally, through the implementation of comprehensive transparency in the entire data management cycle, strict and enforceable regulations, increasing public data literacy as a bulwark against misleading narratives, and the ethical use of digital technology, in order to return policy to a basis of evidence that is fair, accountable, and relevant to the social complexity faced.